MRSA infection of masticatory spaces in a paediatric patient. Issue 2 (10th February 2021) - Singh, Anupam; Smriti, Komal; Nayak, Sunil; Gadicherla, Srikanth
Abstract : Diagnosis of source of maxillofacial infection in paediatric patients can be challenging due to difficulty in eliciting a proper history and multiple potential sources of infection. Identification and removal of the nidus of infection with decompression and institution of antibiotic therapy as per the culture-sensitivity report form the mainstay treatment of the infection. Deviation from it may result in persistence or even progression of infection, resulting in significant morbidity and mortality. In the past decade, the incidence of community-acquired methicillin-resistant Staphylococcus aureus infection in the oral cavity has seen an upward trend. This has further led to an increase in complexity in the diagnosis of maxillofacial infections. In this case, the authors want to bring to light the challenges faced in managing a paediatric patient with persistent fascial space infection even after removal of the offending tooth, which signifies the importance of managing the infection by the time-tested protocol.